Factors affecting safety performance at construction site of Srimuda Jaya Sdn. Bhd. / Lily Shahzlyn Shaharuddin - Shaharuddin, Lily Shahzlyn (Faculty of Business and Management, 2018)
Construction industry play important role in economic sector. However, statistic have shown that there is increasing number of accident year by year. The study is to identify the factor affecting safety performance in construction site at Srimuda Jaya Sdn. Bhd which located at Johor Bahru, Johor. To perform this objective, the research has extracted three independent variables which are: 1) safety awareness, 2) time barriers, and 3) management commitment. Data were obtained by distribute 73 questionnaires which were analyzed by using Likert scale. The respond have been collecting from the manpower, site manager and safety officer in Srimuda Jaya Sdn. Bhd. The sampling technique used is proportionate stratified and random sampling. The data then was analyzed by using Statistical Package for the Social Sciences (SPSS) version 22.0 software. The finding of this research shows that the safety awareness is the most influential factor that affecting safety performance in construction site at Srimuda Jaya Sdn. Bhd as it have the highest beta (β=0.601). Therefore, Srimuda Jaya Sdn. Bhd need to have regular inspection, conduct proper training and effectiveness communication to improve the safety awareness in the company. This research give others construction companies an idea on what factors affecting safety performance and how to improve it.